Venous thromboembolism in surgery: Risk, prevention and treatment - Prego, Alfredo (Cirugía del Uruguay, 1993)
A revision is made of venous thromboembolism related to surgery, emphasizing detection of congenital or acquired alterations in the coagulationlfibrinolysis system. High-risk patients for lower limb venous thrombosis were identified; thrombo-prophylaxis measures are highly recommended in these cases. An up-to-date of thrombosis treatment is made; the option of fibrinolytic therapy remains as an element to be used in selected cases, as a means of decreasing post-phlebitic sequels .